2020
DOI: 10.3390/nano10122434
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Atomic Layer Deposition of GaN on 1D Nanostructures

Abstract: Silica nanosprings (NS) were coated with gallium nitride (GaN) by high-temperature atomic layer deposition. The deposition temperature was 800 °C using trimethylgallium (TMG) as the Ga source and ammonia (NH3) as the reactive nitrogen source. The growth of GaN on silica nanosprings was compared with deposition of GaN thin films to elucidate the growth properties. The effects of buffer layers of aluminum nitride (AlN) and aluminum oxide (Al2O3) on the stoichiometry, chemical bonding, and morphology of GaN thin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 93 publications
(111 reference statements)
0
6
0
Order By: Relevance
“…Therefore, 1D semiconductor nanostructures such as nanowires (NWs), nanorods (NRs), nanopillars, nanocolumns (NCs), and nanotubes (NTs) provide promising potential for the creation of high-performance optoelectronic and electrical devices. 53–56…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, 1D semiconductor nanostructures such as nanowires (NWs), nanorods (NRs), nanopillars, nanocolumns (NCs), and nanotubes (NTs) provide promising potential for the creation of high-performance optoelectronic and electrical devices. 53–56…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, 1D semiconductor nanostructures such as nanowires (NWs), nanorods (NRs), nanopillars, nanocolumns (NCs), and nanotubes (NTs) provide promising potential for the creation of high-performance optoelectronic and electrical devices. [53][54][55][56] Owing to their use in various applications substantial research has been devoted to the growth of 1D GaN NWs. Traditionally, GaN NWs were grown using MBE or MOCVD.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, epitaxial growth of GaN on low‐cost substrates, for example, sapphire, Si, etc., for its commercial uses is justifiable. To grow epitaxial films of GaN on sapphire conventional methods, for example, molecular beam epitaxy (MBE), [ 1 ] metal–organic chemical vapor deposition (MOCVD), [ 8 ] atomic layer deposition (ALD), [ 9 ] metal–organic vapor‐phase epitaxy (MOVPE) [ 10 ] are preferably used due to their due advantages. The use of a pulsed laser deposition (PLD) for growing GaN films is also demonstrated, taking its unique capabilities into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…A suitable deposition technique should be used for the preparation of TiO 2 aeromaterials on the basis of networks of interconnected ZnO microtetrapods. Atomic layer deposition (ALD) is an extremely valuable technique for growing conformal ultrathin films with high accuracy on different substrates [42]. It has been shown that ALD coatings provide a high stability to various functional nanostructures, improving their performance for applications in photovoltaics, electrochemical energy storage, photo-and electro-chemical devices, etc.…”
Section: Introductionmentioning
confidence: 99%